Assessment of facial profile changes in patients treated with maxillary premolar extractions - Renata Rodrigues de Almeida-Pedrin; Luciane Brigueli Marrone Guimarães; Marcio Rodrigues de Almeida; Renato Rodrigues de Almeida; Fernando Pedrin Carvalho Ferreira (Dental Press Editora, 2012)
OBJECTIVE: Evaluate the facial profile changes of orthodontic treatment with extraction of two upper first premolars, from the perspective of orthodontists, dentists and lay people. METHODS: Facial profiles of radiographs taken before and after treatment of 70 patients with Class II, division 1 malocclusion were traced. The silhouettes of the 70 patients were randomly assembled in an album with, being two profiles on each sheet of the same patient. Then, 30 orthodontists, 30 dentists and 30 lay people chose the more esthetic facial profile (A or B), and the amount of change they perceived between the two profiles before and after treatment, according to a visual analog scale (VAS). RESULTS: The results revealed that 83 examiners preferred the post-treatment profiles, and only three dentists and four lay people chose the profiles pre-treatment more frequently. Thus, the orthodontists often chose the profiles after treatment, followed by dentists, with no statistically significant differences found between dentists and lay people. There were significant differences within groups in the preference of pre- and post-treatment profile. Furthermore, the three groups of evaluators indicated that pre and post-treatment profiles did not differ substantially. CONCLUSIONS: The treatment of Class II, division 1 malocclusion with extraction of two first premolars has a positive effect on facial profile esthetics. OBJETIVO: avaliar as alterações do perfil facial decorrentes do tratamento ortodôntico com extrações de dois primeiros pré-molares superiores, sob a óptica de ortodontistas, cirurgiões-dentistas e leigos. MÉTODOS: foram traçados os perfis faciais das telerradiografias pré- e pós-tratamento de 70 pacientes com má oclusão de Classe II, divisão 1, e foi montado um álbum com as silhuetas dos 70 pacientes, de forma aleatória, sendo dois perfis em cada folha do mesmo paciente. A seguir, 30 ortodontistas, 30 cirurgiões-dentistas e 30 leigos escolheram o perfil facial mais estético (A ou B), e a quantidade de alteração que percebiam entre os dois perfis pré- e pós-tratamento, de acordo com a escala visual analógica (EVA). RESULTADOS: os resultados revelaram que 83 examinadores preferiram o perfil pós-tratamento, sendo que somente três cirurgiões-dentistas e quatro leigos escolheram com maior frequência os perfis pré-tratamento. Assim, os ortodontistas escolheram mais frequentemente os perfis pós-tratamento, seguidos pelos cirurgiões-dentistas, sem diferença estatisticamente significativa entre cirurgiões-dentistas e leigos. Houve diferença estatisticamente significativa intragrupos na preferência do perfil pré- e pós-tratamento. Além disso, os três grupos de avaliadores indicaram que os perfis pré- e pós-tratamento não diferiram substancialmente. CONCLUSÕES: o tratamento da má oclusão de Classe II, divisão 1, com extração de dois primeiros pré-molares produziu um efeito positivo na estética do perfil facial.